MicroRNA as a potential diagnostic and prognostic biomarker in brain gliomas: a systematic review and meta-analysis - Hasani, Fatemeh; Masrour, Mahdi; Jazi, Kimia; Ahmadi, Payam; Hosseini, Saba sadat; Lu, Victor M.; Alborzi, Amirmohammad (Frontiers in Neurology, 2024)
Introduction Brain neoplasms and central nervous system (CNS) disorders, particularly gliomas, have shown a notable increase in incidence over the last three decades, posing significant diagnostic and therapeutic challenges. MicroRNAs (miRNAs) have emerged as promising biomarkers due to their regulatory role in gene expression, offering potential enhancements in glioma diagnosis and prognosis. Methods This systematic review and meta-analysis, adhering to PRISMA guidelines, included 25 studies for diagnostic accuracy and 99 for prognostic analysis, published until August 27th, 2023. Studies were identified through comprehensive searches of PubMed, Web of Science, and Scopus databases. Inclusion criteria encompassed peer-reviewed original research providing sensitivity, specificity, and area under the curve (AUC) for miRNAs in glioma diagnosis, as well as survival outcomes with hazard ratios (HRs) or mean survival. Results and discussion Meta-analysis demonstrated miRNAs’ high diagnostic accuracy, with a pooled sensitivity of 0.821 (95% CI: 0.781–0.855) and specificity of 0.831 (95% CI: 0.792–0.865), yielding an AUC of 0.893. Subgroup analysis by specimen type revealed consistent accuracy across blood, cerebrospinal fluid (CSF), and tissue samples. Our results also showed miRNAs can be potential prognostic biomarkers. miRNAs showed significant associations with overall survival (OS) (pooled HR: 2.0221; 95% CI: 1.8497–2.2105), progression-free survival (PFS) (pooled HR: 2.4248; 95% CI: 1.8888–3.1128), and disease-free survival (DFS) (pooled HR: 1.8973; 95% CI: 1.1637–3.0933) in tissue specimens. These findings underscore miRNAs’ potential as valuable biomarkers for improving glioma diagnosis and prognosis, offering insights for enhancing clinical decision-making and patient outcomes.